PENGEMBANGAN MODUL BIMBINGAN DAN KONSELING TENTANG REGULASI DIRI SISWA DALAM HUBUNGAN SOSIAL - Ita Karina Bancin; Mudjiran -; Rusdinal - (Universitas Sultan Ageng Tirtayasa, 2017)
Self regulation is one way to improve students' understanding of good social relations. This research aimed to formulate module, to describe the level of applicability, and to describe the effectiveness of the guidance and counseling module on student self-regulation in social relations. The method used was ADDIE model development. The subjects of the research werethree experts, three counselors and 23 students. The instruments used were questionnaire. The research was conducted by research product trial. The data of the research were analyzed by using the Coefficient Concordance test of Kendall's W and Wilcoxon Signed Ranks Test. The result of the research showed that the module on self-regulation of students in social relation was considered feasible to be utilized by counselor, the practicality degree of the module on self-regulation of students in social relations was highly valued for use by students, and there was a change of understanding of students before and after using the counseling guidance module on student self-regulation in social relations. Keywords: Self Regulation, Social Relations, Module.Self regulation is one way to improve students' understanding of good social relations. This research aimed to formulate module, to describe the level of applicability, and to describe the effectiveness of the guidance and counseling module on student self-regulation in social relations. The method used was ADDIE model development. The subjects of the research werethree experts, three counselors and 23 students. The instruments used were questionnaire. The research was conducted by research product trial. The data of the research were analyzed by using the Coefficient Concordance test of Kendall's W and Wilcoxon Signed Ranks Test. The result of the research showed that the module on self-regulation of students in social relation was considered feasible to be utilized by counselor, the practicality degree of the module on self-regulation of students in social relations was highly valued for use by students, and there was a change of understanding of students before and after using the counseling guidance module on student self-regulation in social relations. Keywords: Self Regulation, Social Relations, Module.